PELANGGARAN KODE ETIK PROFESI POLISI DI INDONESIA - Rahman, Maulana Malikul (Universitas 17 Agustus 1945 Samarinda, 2025)
ABSTRACT. One of the cases of ethical code violations that has gained public attention is the involvement of certain police officers in the abuse of power and excessive violence against the community. Violations of the police professional code of ethics are not only caused by individual weaknesses but also indicate systemic weaknesses in the oversight and internal law enforcement mechanisms of the National Police. This research discusses the imposition of sanctions on violations of police ethics and the challenges faced in implementing sanctions for violations of police ethics in Indonesia. The type of research used by the author is normative research. Normative legal research is legal research conducted by examining library materials. The imposition of sanctions for violations of the police code of ethics, in accordance with Perpol Number 7 of 2022, aims to maintain professionalism, integrity, and public trust in the National Police. These challenges include overlaps in authority with other law enforcement agencies, limitations in resources and infrastructure, as well as threats or intimidation from interested parties. Furthermore, the obstacles faced in the application of sanctions for violations of the police code of ethics in Indonesia still encounter various hurdles, including weaknesses in internal supervision, an organizational culture that is difficult to change, social and political pressures, and a lack of transparency in the sanctioning process. Keywords: Violation, Code of Ethics, Police.